Human cystatin C induces the disaggregation process of selected amyloid beta peptides: a structural and kinetic view - Adriana Żyła; Anne Martel; Przemysław Jurczak; Augustyn Moliński; Aneta Szymańska; Maciej Kozak (Scientific Reports, 2023)
Abstract Neurodegenerative diseases, such as Alzheimer’s disease (AD) and various types of amyloidosis, are incurable; therefore, understanding the mechanisms of amyloid decomposition is crucial to develop an effective drug against them for future therapies. It has been reported that one out of three people over the age of 85 are suffering from dementia as a comorbidity to AD. Amyloid beta (Aβ), the hallmark of AD, transforms structurally from monomers into β-stranded aggregates (fibrils) via multiple oligomeric states. Astrocytes in the central nervous system secrete the human cystatin C protein (HCC) in response to various proteases and cytokines. The codeposition of Aβ and HCC in the brains of patients with AD led to the hypothesis that cystatin C is implicated in the disease process. In this study, we investigate the intermolecular interactions between different atomic structures of fibrils formed by Aβ peptides and HCC to understand the pathological aggregation of these polypeptides into neurotoxic oligomers and then amyloid plaques. To characterize the interactions between Aβ and HCC, we used a complementary approach based on the combination of small-angle neutron scattering analysis, atomic force microscopy and computational modelling, allowing the exploration of the structures of multicomponent protein complexes. We report here an optimized protocol to study that interaction. The results show a dependency of the sequence length of the Aβ peptide on the ability of the associated HCC to disaggregate it.